MEDICATION ERRORS IN THE PRESCRIBING AND TRANSCRIBING PHASE: CASE STUDY - MUHAMMAD ROYANUL FIRDAUS; Lutfi Qamari; Ana Zakiyah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Medication errors are a leading cause of patient safety incidents in primary healthcare facilities and often occur during the prescribing and transcribing phases , the initial stages of the medication use process. This case study aims to examine in-depth a medication error incident involving the erroneous prescription of gentamicin skin ointment for an eye complaint in a patient. Data were collected through medical record reviews, documentation audits, incident reports, and in-depth interviews with healthcare workers involved in the prescribing, transcribing, and dispensing processes. The study results revealed several discrepancies in the prescribing phase , including illegible prescriptions, incomplete drug names, omissions of instructions for use, and the omission of important clinical information such as allergy history, prescription date, and patient physiological parameters. In the transcribing phase , errors occurred due to incorrectly transcribing the drug name and instructions for use. Systemic factors contributing to this incident include high workload, limited human resources, and suboptimal implementation of medication safety procedures in accordance with national pharmaceutical service standards. These findings emphasize the importance of improving prescription clarity, strengthening verification mechanisms, and adherence to SOPs in efforts to minimize medication errors and strengthen patient safety.